Dietary menhaden fish oil supplementation suppresses lipopolysaccharide-induced neuroinflammation and cognitive impairment in diabetic rats - Titisari, Nurina; Fauzi, Ahmad; Abdul Razak, Intan Shameha; Mohd Noor, Mohd Hezmee; Samsulrizal, Nurdiana; Ahmad, Hafandi (Taylor and Francis Group, 2024)
Context: Menhaden fish oil (FO) is widely recognized for inhibiting neuroinflammatory responses and preserving brain function. Nevertheless, the mechanisms of FO influencing brain cognitive function in diabetic states remain unclear. Objective: This study examines the potential role of FO in suppressing LPS-induced neuroinflammation and cognitive impairment in diabetic animals (DA). Materials and methods: Thirty male Wistar rats were divided into 5 groups: i) DA received LPS induction (DA-LPS); ii) DA received LPS induction and 1 g/kg FO (DA-LPS-1FO); iii) DA received LPS induction and 3 g/kg FO (DA-LPS-3FO); iv) animals received normal saline and 3 g/kg FO (NS-3FO) and v) control animals received normal saline (CTRL). Y-maze test was used to measure cognitive performance, while brain samples were collected for inflammatory markers and morphological analysis. Results: DA received LPS induction, and 1 or 3 g/kg FO significantly inhibited hyperglycaemia and brain inflammation, as evidenced by lowered levels of pro-inflammatory mediators. Additionally, both DA-LPS-1FO and DA-LPS-3FO groups exhibited a notable reduction in neuronal damage and glial cell migration compared to the other groups. These results were correlated with the increasing number of entries and time spent in the novel arm of the Y-maze test. Discussion and conclusion: This study indicates that supplementation of menhaden FO inhibits the LPS signaling pathway and protects against neuroinflammation, consequently maintaining cognitive performance in diabetic animals. Thus, the current study suggested that fish oil may be effective as a supporting therapy option for diabetes to avoid diabetes-cognitive impairment.